PRESENCE OF LYMNAEIDAE SNAILS WITH LARVAE OF F. HEPATICA IN ALTITUDES OVER 4000 M ABOVE SEA LEVEL IN THE SOUTHERN HIGHLANDS OF PERU - Londoñe B., Pablo (2009)
The objective of the study was to determine the presence of F. hepatica larvae and the species of snails that are intermediary hosts of F. hepatica in altitudes over 4000 m above the sea level (masl). The study covered three altitudes (4000-4200, 4200-4300, 4300-4500 masl) and was collected 150 snails per each altitude during the rainy season (January-March, 2004). The area is part of La Raya Experimental Research Station of San Antonio de Abad University, Cusco. Fifty snails were used for measuring the shell, 50 for observing the reproductive organs and the radula to identify the species, and 50 to observe the larva forms of Fasciola hepatica. Snails found at 4000-4200 masl were of the Lymnaea viatrix species and at 4200-4500 of the Pseudosuccinea columella species. The level of infestation with larva forms of Fasciola hepatica was 48, 46 and 36% at 4000-4200, 4200-4300, and 4300-4500 masl respectively, and this shows that the parasite can survive over 4000 masl. The relationship between level of infestation and altitude was inversely proportional.